2021
DOI: 10.1186/s12891-021-04251-3
|View full text |Cite
|
Sign up to set email alerts
|

Exploring expectations and perceptions of different manual therapy techniques in chronic low back pain: a qualitative study

Abstract: Background Chronic low back pain (CLBP) prevalence has steadily increased over the last two decades. Manual therapy (MT) is recommended within a multimodal management approach to improve pain and disability although evidence investigating the patients’ experience of MT is scarce. Objective To explore expectations and perceptions of MT techniques in people with CLBP. Methods A qualitative study embedded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Exploring expectations and perceptions of different manual therapy techniques in chronic low back pain, Plank et al (Plank et al, 2021) showed that a treatment technique is perceived as positive if its characteristics align with the individual's understanding of pain and if care is provided in an informative and reassuring manner.…”
Section: Expectations Of Resultsmentioning
confidence: 99%
“…Exploring expectations and perceptions of different manual therapy techniques in chronic low back pain, Plank et al (Plank et al, 2021) showed that a treatment technique is perceived as positive if its characteristics align with the individual's understanding of pain and if care is provided in an informative and reassuring manner.…”
Section: Expectations Of Resultsmentioning
confidence: 99%
“…Participants in this cohort expressed a lack of alignment between their pain experience and their expectations. These sentiments highlight the individualized experience and need to enhance patient preparedness and improve counseling related to expectations and management options 24–26 . In September 2021, ACOG released a consensus statement endorsing the importance of individualized management of postpartum pain 27 .…”
Section: Discussionmentioning
confidence: 99%
“…These sentiments highlight the individualized experience and need to enhance patient preparedness and improve counseling related to expectations and management options. [24][25][26] In September 2021, ACOG released a consensus statement endorsing the importance of individualized management of postpartum pain. 27 Participants in this study echoed this imperative by demonstrating the individual nature of the pain experience and varying preferences regarding whether, when, and how to treat their postpartum pain.…”
Section: Discussionmentioning
confidence: 99%
“…To effectively deal with such barriers, physiotherapists need not only to know the current evidence but also to be able to engage patients in complex conversations, reframe their beliefs, suggest alternative treatment options, and develop a strong therapeutic alliance (Plank et al., 2021). Physiotherapists need the support of their professional organisations and must engage them in public awareness campaigns and advocacy efforts aligned with marketing and communication messages that promote EBP.…”
Section: Discussionmentioning
confidence: 99%